P2.130 Penile Mondor's Disease: An Underdiagnosed and Under-Reported Benign Condition. (13th July 2013) - Kumar, B
Abstract : Bhushan Kumar, Abir Saraswat, BD Radotra, Tarun Narang Background: Mondor's disease of the penis is usually a benign, self-limiting process of acute onset; associated with considerable psychological stress and sexual disharmony. Although it is not so uncommon, there have been few large studies. Methods: A retrospective review of 37 patients with penile Mondor's disease over a period of 2002–2010 was done. Detailed history and clinical findings were recorded. Histopathological examination and staining with CD31 and CD34 monoclonal antibodies was also done in 17 patients. Patients were followed up to see the response to treatment and recurrences. The age of these patients ranged from 20–44 years. The patients presented with cord-like thickening on penis within 24–48 hours after a prolonged sexual act with or without an intercourse. Seventeen patients had history of one or more episodes of STDs at presentation or in the past. Histopathological specimens showed prominent vessels with plump endothelial cells and thickened blood vessel walls. Occasional vessel showed complete occlusion of its lumen. Doppler US done in 10 patients showed dorsal vein thrombosis without the flow signals in this area. Patients were treated with counselling, abstinence and paracetamol. Thirty patients had resolution of the swelling by 6–8 weeks with treatment only two patient required surgery. No recurrence or erectile dysfunction was noted in any of the patients in the follow up from 2 to 8 years. Conclusions: Penile Mondor's disease has a favourable evolution and functional prognosis;although various etiologies have been proposed; trauma caused by sexual intercourse or masturbation is the main etiologic factor. Doppler US is a non invasive diagnostic modality helpful in both diagnosis and follow-up, however further analysis of Doppler US findings in a larger number of cases needs to be done to elucidate the hemodynamic changes in this not so rare entity.